2020
DOI: 10.3989/scimar.04945.27a
|View full text |Cite
|
Sign up to set email alerts
|

Seabed litter distribution in the high seas of the Flemish Pass area (NW Atlantic)

Abstract: Seabed litter of the Flemish Pass area (NW Atlantic Ocean) was analysed and described using data from the EU-Spain groundfish survey (2006-2017 period). This study presents baseline information on seabed litter in this area. The Flemish Pass is located in areas beyond national jurisdiction within the Northwest Atlantic Fisheries Organization Regulatory Area Division 3L. A total of 1169 valid bottom trawl hauls were analysed (104-1478 m depth). Litter was found in 8.3% of the hauls, with mean densities of 1.4±0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
2
1
0
Order By: Relevance
“…The observed dominance of plastic items in the survey catches is comparable to most studies on seafloor litter (Alvito et al 2018;García-Alegre et al 2020;Kammann et al 2018;Spedicato et al 2019;Meyerjürgens et al 2022). Many studies reported that most of the litter items found on the seafloor originated from the fishing industry, dominated by fishing lines (e.g.…”
Section: Comparison Ibts and Btssupporting
confidence: 82%
“…The observed dominance of plastic items in the survey catches is comparable to most studies on seafloor litter (Alvito et al 2018;García-Alegre et al 2020;Kammann et al 2018;Spedicato et al 2019;Meyerjürgens et al 2022). Many studies reported that most of the litter items found on the seafloor originated from the fishing industry, dominated by fishing lines (e.g.…”
Section: Comparison Ibts and Btssupporting
confidence: 82%
“…A low correlation between fishing activities and marine litter has also been reported by other authors (Buhl-Mortensen and Buhl-Mortensen, 2018;Garcı ́a-Alegre et al, 2020) and may be explained by different factors. First, the number of recorded litter is often low with high variability resulting in a lack of power and hampering the detection of correlations.…”
Section: Impact Of Human Activities On the Litter Distributionsupporting
confidence: 66%
“…Although studies on this issue have exponentially increased during recent years, there is still a high degree of uncertainty on oceanic MPs distribution, especially for remote offshore areas and deep seas (Galgani et al, 2021). Plastic debris is recurrently trapped in bottom-trawls gears even at depths below 1400 m (García-Alegre et al, 2020) and MPs have been identified in sediment samples collected at about 5700 m depth (Fischer et al, 2015). It is universally accepted that litter pollution is increasing globally, even in natural sanctuaries, where important accumulations of macro, meso and microdebris were identified, with risk for the entire ecosystem of this protected reserves (Bauer et al, 2008;Macieira et al, 2021;Scopetani et al, 2021).…”
mentioning
confidence: 99%